2012
DOI: 10.1002/mar.20559
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Attribute Importance in the Effects of Option Framing on Choice: Budget Range and Justification as Moderators of Loss Aversion

Abstract: Loss aversion or an endowment-based explanation clearly predicts that subtractive option framing (i.e. deleting mode or starting from a full model) will have a stronger effect on choice than additive option framing (i.e. adding mode or starting from a base model). This research examines whether the differential effects of option framing (additive vs. subtractive) on choice vary depending on the importance of attributes that constitute the defaults. Furthermore, this research proposes that consumers' budget ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 36 publications
3
14
0
Order By: Relevance
“…Therefore, based on the above theories, we make a prediction that consumers' pain perception caused by deleting the "owed" options in the -OF condition is higher than the entertainment consumers perceive in the +OF condition because of acquiring the option value through adding options (Park and Kim, 2012;Biswas and Grau, 2008;Krishna and Krishna, 2005;Levin et al, 2002;Park et al, 2000). That is to say, consumers engaged in -OF (versus +OF) tend to perceive the task of making option choices as more difficult and mental conflict (Park et al, 2000;Park and Kim, 2012), so that they will spend more thinking time doing more information processing on product options (Luce and Bettman, 1997;Carmon and Ariely, 2000;Park et al, 2000;Jin et al, 2009), which should lengthen the decision time consumers spend in the -OF condition.…”
Section: The Effect Of Option Framing On Decision Time: the Regulatormentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, based on the above theories, we make a prediction that consumers' pain perception caused by deleting the "owed" options in the -OF condition is higher than the entertainment consumers perceive in the +OF condition because of acquiring the option value through adding options (Park and Kim, 2012;Biswas and Grau, 2008;Krishna and Krishna, 2005;Levin et al, 2002;Park et al, 2000). That is to say, consumers engaged in -OF (versus +OF) tend to perceive the task of making option choices as more difficult and mental conflict (Park et al, 2000;Park and Kim, 2012), so that they will spend more thinking time doing more information processing on product options (Luce and Bettman, 1997;Carmon and Ariely, 2000;Park et al, 2000;Jin et al, 2009), which should lengthen the decision time consumers spend in the -OF condition.…”
Section: The Effect Of Option Framing On Decision Time: the Regulatormentioning
confidence: 99%
“…For instance, based on a meta-analysis of 136 studies, Kühberger (1998) found that although student samples dominate framing research, the behavior of student participants does not differ from that of non-student participants (Clawson et al, 1997). In addition, Park and Kim et al (2012) chose undergraduates as subjects and got satisfactory outcome in the research about product and service There are four phases in the process of online service customization experiment: the first stage is to let subjects enter the website, register an account and fill in their personal information which includes name, age, gender, class, student ID and phone number, etc. ; The second stage is to make subjects be familiar with the background information and rules of the customization task and the function of every option, at the same time they were asked to assess the preference and perceived importance of a variety of service options, as well as the expectation for the number of options they planned to choose on a sevenpoint scale; The third stage is the formal customization process, the subjects need to add or delete options, and eventually form their own mobile communication package; The fourth stage is to ask for suggestions and express our sincere gratitude to subjects.…”
Section: Pretesting and Website Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…With respect to how consumers construct their bundle, option framing has also been identified as an important moderator of choice. Studies have shown that choices are likely to differ depending on whether consumers are asked to add options to a base model or to delete options from a fully loaded model (Park, Jun, & MacInnis, ; Park & Kim, ). These two basic aspects of product bundling in the arts and culture domain are examined in the present study and are discussed in the next two sections.…”
Section: The What and How Of Bundling In The Artsmentioning
confidence: 99%